Pengaruh Dukungan Sosial Orang Tua terhadap Prestasi Belajar Siswa Kelas IX pada Mata Pelajaran IPS di MTs Azziyadatul Hasanat Bekasi - Ishomudin, Ahmad (Arden Jaya Publisher, 2023)
This study aims to determine the effect of parental social support on class VIII student achievement in social studies subjects at MTS Azziyadatul Hasanat. The research method used is to use an associative quantitative method. The techniques of taking sample using random sampling with a sample of 68 students in Angkasa Junior High School Halim Perdana Kusuma in East Jakarta. The data used is the regression correlation analysis of Y and X for Y = - 9.698 + 0.996 X. it’s can be seen from the calculation of simple ANOVA. Significant correlation coefficient tests were obtained from the model summary table. Seen in the first line the correlation coefficient (rxy) = 0. 995 and Fhit (Fchange) = 6580.157 and p-value = 0.000 < 0.05. This means Ho is rejected. Thus, the correlation coefficient X and Y are significant. While the correlation coefficient of determination from the model summary table in the second row, namely R square = 0.990 which means that 99 % of the variation in the social studies achievement variable is influenced by social support from parents. There is the influence of social support parents of students' learning achievement, it can be seen from the regression equation Y = -9.698 + 0.996 X. From analysis results is t-hit 81.118 and p-value of 0.00 / 2 < 0.05 or Ho rejected. Thus